Incidental mucosal abnormalities of paranasal sinus in patients referred for MRI brain for suspected intracranial pathology in Eastern Nepal - Gupta, Mukesh Kumar; Rauniyar, Raj Kumar; Ahmad, Kaleem; Ansari, Sajid; Pant, Ashok Raj (Asian Journal of Medical Sciences, 2014)
Background: Mucosal abnormalities of the paranasal sinuses are frequently encountered as incidental findings during MRI evaluation of brain, however, little is known about their magnitude and spectrum in the Nepalese population. The purpose of this study was to analyze the spectrum of incidental mucosal abnormalities of paranasal sinuses in patients who had undergone MRI of brain for suspected intracranial pathologies. Methods: A retrospective cross-sectional study was conducted on 600 consecutive patients referred for brain MRI with suspicion of intracranial pathologies over a period of two years. The mucosal abnormalities of paranasal sinuses were evaluated and the findings were categorized according to the anatomic location and the imaging features of the abnormality seen on MRI. Results: Of total 600 cases, sinus abnormality was seen in 349(58.2%) patients. The spectrum of sinus abnormalities in 349 patients was as follows: mucosal thickening - 313(89.7%), polyp/retention cyst - 139(39.8%), sinus opacification - 114(32.7%), and fluid level - 23(6.6%). Maxillary sinus was involved in 291(83.4%) followed by ethmoid in 257(73.6%), frontal in 169(48.4%) and sphenoid sinus in 115(33.0%) cases. Conclusion: Incidental mucosal abnormalities of paranasal sinus are common findings on MRI performed for evaluation of intracranial pathologies. Mucosal thickening is the commonest abnormality and the maxillary sinus is the most commonly affected sinus. Such a high prevalence of incidental abnormality suggests some unidentified subtle environmental allergens in this part of Nepal and the condition may reflect initial findings of allergic rhinosinusitis before it progresses to the full-fledged symptomatic stage. Asian Journal of Medical Science, Volume-5(3) 2014: 40-44 http://dx.doi.org/10.3126/ajms.v5i3.9929